Teach yourself visually Photoshop CC - Wooldridge, Mike (Teach yourself visually., 2013)
This visual guide includes step-by-step instructions, for Photoshop newcomers as well as experienced users looking for some beginning to intermediate-level techniques, to give their projects the "wow" factor!